MODELLING COMMODITY FUTURES PRICES: THE CASE OF CRUDE PALM OIL FUTURES - Khalil Ahmed; Zurina Shafii; Amir Shaharuddin; Siti Nurazira Mohd (Asian Academy of Management Journal, 2019)
The present paper seeks to fulfil the gap of knowledge in crude palm oil futures (FCPO) by employing unobserved component (UC) methodology. It may perhaps be the first study in Malaysian capital market to examine FCPO prices using UC model. The empirical results indicate that FCPO presents a permanent behaviour. The transitory component exhibits a higher degree of persistence with a periodicity of approximately one year. In addition, the model of the study has proven its ability to capture unobserved characteristics of FCPO’s time series price and has shown a satisfactory performance for the sampled period in terms of fit. This study implicates that understanding the cyclical pattern, duration, and persistence provides important information that would help to create an appropriate strategy to manage risks, smooth and stabilise returns over the FCPO cycle. Such a strategy would ensure the stability and sustainability of the FCPO market.